A Form of Apolipoprotein A‐I Is Found Specifically in Relapses of Focal Segmental Glomerulosclerosis Following Transplantation. Issue 2 (3rd December 2012) - Lopez‐Hellin, J.; Cantarell, C.; Jimeno, L.; Sanchez‐Fructuoso, A.; Puig‐Gay, N.; Guirado, L.; Vilariño, N.; Gonzalez‐Roncero, F. M.; Mazuecos, A.; Lauzurica, R.; Burgos, D.; Plumed, J. S.; et al.
<x xml:space="preserve">Abstract</x> Recurrence of idiopathic focal segmental glomerulosclerosis (FSGS) following kidney transplantation occurs in a large percentage of patients. Accurate prediction of recurrence and elucidation of its pathogenesis are major therapeutic goals. To detect differential proteins related to FSGS recurrence, proteomic analysis was performed on plasma and urine samples from 35 transplanted idiopathic FSGS patients, divided into relapsing and nonrelapsing. Several proteins were detected increased in urine of relapsing FSGS patients, including a high molecular weight form of apolipoprotein A‐I, named ApoA‐Ib, found exclusively in relapsing patients. This finding was verified by Western blot individually in the 35 patients and validated in an independent group of 40 patients with relapsing or nonrelapsing FSGS, plus two additional groups: FSGS‐unrelated patients showing different proteinuria levels (n = 30), and familial FSGS transplanted patients (n = 14). In the total of 119 patients studied, the ApoA‐Ib form was detected in 13 of the 14 relapsing FSGS patients, and in one of the 61 nonrelapsing patients. Only one of the 30 patients with FSGS‐unrelated proteinuria tested positive for ApoA‐Ib, and was not detected in familial patients. Urinary ApoA‐Ib is associated with relapses in idiopathic FSGS and warrants additional investigation to determine its usefulness as biomarker of relapse following transplantation.